Internet addiction among students STML in UUM - Wan Abdul Razak, Wan Nor Iezatulerma; Mat Yamin, Fadhilah (Universiti Utara Malaysia, 2020)
The purpose of this study was to identify the level of internet addiction among undergraduate students. Internet addiction has become an increasingly serious problem among university students. This study was conducted using quantitative method. The questionnaires was distributed to STML undergraduate students through the “Google Form” application. The findings from this study found that STML undergraduate students are having internet addiction problem. Excessive use of the Internet will cause internet addiction problems among students especially university students who use the internet. Therefore, it is recommended that awareness programs on Internet use be conducted to prevent students from becoming addicted to negatively affect their educational performance and social life.